Longitudinal Label‐Free Two‐Photon Microscopy of Cellular Healing Processes in Non‐Ablative Fractional Laser Wounds. Issue 10 (17th June 2021) - Kim, Seonghan; Le, Viet‐Hoan; Kim, Bumju; Kim, Chan Johng; Im, Sin‐Hyeog; Kim, Ki Hean
Abstract : Background and Objectives: Wound healing is an important biomedical problem with various associated complications. Although cutaneous wound healing has been studied in vivo extensively using various optical imaging methods, early‐stage cellular healing processes were difficult to study due to scab formation. The objective of this study is to demonstrate that minimal laser wounds and optical microscopy can access the detailed cellular healing processes of cutaneous wounds from the early stage. Study Design/Materials and Methods: A non‐ablative fractional laser (NAFL) and label‐free two‐photon microscopy (TPM) were used to induce minimal cutaneous wounds and to image the wounds in three‐dimension. Sixteen hairless mice and a single human volunteer were used. NAFL wounds were induced in the hindlimb skin of the mice and in the forearm skin of the human subject. The NAFL wounds were longitudinally imaged during the healing period, starting from an hour post wound induction in the earliest and until 21 days. Cells in the wound and surrounding normal skin were visualized based on two‐photon excited auto‐fluorescence (TPAF), and cellular changes were tracked by analyzing longitudinal TPM images both qualitatively and quantitatively. Damage and recovery in the skin dermis were tracked by using the second harmonic generation (SHG) signal of collagen. Immunofluorescence and hematoxylin and eosin histology analysis were conducted to validate the TPM results of the murine skin. Results: Cellular healing processes in NAFL wounds and surroundings could be observed by longitudinal TPM. In the case of murine skin, various healing phases including inflammation, re‐epithelization, granulation tissue formation, and late remodeling phase including collagen regeneration were observed in the same wounds owing to minimal or no scab formation. The re‐epithelization process was analyzed quantitatively by measuring cell density and thickness of the epithelium in the wound surroundings. In the case of the human skin, the access inside the wound was blocked for a few days post wound induction due to scabs but the cellular changes in the wound surroundings were observed from the early stage. Cellular healing processes in the NAFL wound of the human skin were similar to those in murine skin. Conclusions: The minimal NAFL wound model and label‐free TPM demonstrated the cell level assessment of wound healing processes with applicability to human subjects. © 2021 Wiley Periodicals LLC.